DEVELOPING BARRIER-FREE COMPETENCE IN FUTURE SOCIAL WORK PROFESSIONALS - KOMAR, Iryna (Mountain School of Ukrainian Carpaty, 2025)
The article examines the process of developing barrier-free competence among future social work professionals as a key factor in ensuring inclusivity and accessibility of social services. The importance of forming barrier- free competence as a core component of professional training for future social specialists is substantiated. The concept of barrier-free accessibility is understood as a complex social phenomenon encompassing physical, informational, psychological, communicative, and other aspects of accessibility, thus requiring an interdisciplinary approach to its study and implementation. Barrier-free competence is defined as an integrated set of knowledge, skills, values, and attitudes that enable a specialist to identify and overcome barriers in client interactions, build an inclusive environment, and support the participation of all population groups in social life. The article analyzes its structural components, which includes cognitive, operational-activity, emotional-value, and communicative components. Attention is drawn to defining the content structure of competence, combining knowledge, practical skills, value orientations, and communicative abilities necessary to overcome diverse barriers in professional practice. The possibilities of integrating barrier- free topics into the process of professional training are analyzed, emphasizing the importance of applying an interdisciplinary approach, active teaching methods, and practical engagement with target groups. Recommendations are proposed for improving educational programs and the educational environment to develop socially responsible, competent professionals. It is concluded that effective formation of barrier-free competence is possible only through comprehensive transformation of the educational process: from updating program content and implementing active teaching methods to changing the educational environment and involving students in real practices of inclusive interaction. Training specialists capable of acting within the logic of barrier-free accessibility is not only a requirement of modern professional ethics but also a prerequisite for social cohesion, justice, and sustainable development.